2019
DOI: 10.1111/tid.13203
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus‐6B infection in pediatric allogenic hematopoietic stem cell transplant patients: Risk factors and encephalitis

Abstract: Background Human herpesvirus‐6B (HHV‐6B) infection after allogenic hematopoietic stem cell transplantation (allo‐HSCT) is known to be associated with post‐transplant limbic encephalitis in adults. Meanwhile, the association between HHV‐6B infection and central nervous system complications remains unclear in pediatric allo‐HSCT patients. Methods In this study, HHV‐6B infection was monitored for more than 50 days after HSCT using virus isolation and real‐time PCR. Clinical information such as patient background … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…Other proposed theories for variation in detection rates include different monitoring durations, variation in risk factors across different source populations, different PCR assay sensitivity or practices (eg, use of whole blood vs plasma), and differing viral load cut-offs. 12,13 Our detection rate of HHV-6 at 8.5% (38/445) is low compared to other similar cohorts 1,6,14,15 and likely reflects non-routine HHV-6 testing in our cohort.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Other proposed theories for variation in detection rates include different monitoring durations, variation in risk factors across different source populations, different PCR assay sensitivity or practices (eg, use of whole blood vs plasma), and differing viral load cut-offs. 12,13 Our detection rate of HHV-6 at 8.5% (38/445) is low compared to other similar cohorts 1,6,14,15 and likely reflects non-routine HHV-6 testing in our cohort.…”
Section: Discussioncontrasting
confidence: 57%
“…Cord blood transplants are known to be at a high risk of HHV-6 reactivation due to the absence of HHV-6-specific T cells in cord blood. 15,20,28 We demonstrated a high percentage of cord transplants amongst episodes affected by HHV-6 compared to the other viruses. Given, however, that routine screening was not performed for HHV-6, this may also reflect a surveillance bias to test cord transplants for HHV-6 reactivation.…”
Section: Discussionmentioning
confidence: 71%
“…By contrast, a limited number of pediatric patients with PALE have been reported to date [31]. Our recent retrospective study showed a low prevalence of HHV-6B encephalitis in pediatric HSCT recipients [32]. It has been suggested that HHV-6B infection is associated with mild cognitive impairment in pediatric HSCT recipients [33].…”
Section: Introductionmentioning
confidence: 83%
“…As described above, our recent retrospective study demonstrated that HHV-6B-associated CNS disease in pediatric HSCT recipients occurs less frequently than that in adult HSCT recipients. The clinical symptoms also differ between pediatric and adult HSCT recipients [32]. It is possible that mild cognitive impairment caused by HHV-6B infection may be missed in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 A low frequency (0.5%) of HHV-6 encephalitis despite a high rate (34%) of HHV-6 infection was reported with active monitoring in 219 pediatric HCT patients in Japan. 12,13…”
Section: Hhv-6mentioning
confidence: 99%